2018
DOI: 10.1038/s41416-018-0020-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacodynamic/exposure characterisation of the multikinase inhibitor ilorasertib (ABT-348) in a phase 1 dose-escalation trial

Abstract: BackgroundIlorasertib (ABT-348) inhibits Aurora and VEGF receptor (VEGFR) kinases. Patients with advanced solid tumours participated in a phase 1 dose-escalation trial to profile the safety, tolerability, and pharmacokinetics of ilorasertib.MethodsIlorasertib monotherapy was administered at 10–180 mg orally once daily (Arm I, n = 23), 40–340 mg orally twice daily (Arm II, n = 28), or 8–32 mg intravenously once daily (Arm III, n = 7), on days 1, 8, and 15 of each 28-day cycle.ResultsDose-limiting toxicities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…In particular, CDK4/6 inhibitors palbociclib, ribociclib (Frankell et al 2019) and abemaciclib have shown efficacy in in vitro models of EAC (Frankell et al 2019; Kosovec et al 2017) and promising results in breast cancer, non-small cell lung cancer and melanoma patients (Patnaik et al 2016). Similarly, the use of ABT-348, a multitarget Aurora kinase and VEGFR inhibitor (Maitland et al 2018), is currently being explored in phase I and II clinical trials in patients with CDKN2A -deficient tumors (Sharma 2015; Hong 2015), suggesting additional targeted therapies to this axis are closer to clinical adoption.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, CDK4/6 inhibitors palbociclib, ribociclib (Frankell et al 2019) and abemaciclib have shown efficacy in in vitro models of EAC (Frankell et al 2019; Kosovec et al 2017) and promising results in breast cancer, non-small cell lung cancer and melanoma patients (Patnaik et al 2016). Similarly, the use of ABT-348, a multitarget Aurora kinase and VEGFR inhibitor (Maitland et al 2018), is currently being explored in phase I and II clinical trials in patients with CDKN2A -deficient tumors (Sharma 2015; Hong 2015), suggesting additional targeted therapies to this axis are closer to clinical adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I trial with ilorasertib showed two clinical responses among 58 treated patients, and confirmed a good tolerability and safety profile of the drug (Maitland et al, 2018). Palbociclib, together with abemaciclib and ribociclib, have already been approved for the treatment of metastatic breast cancer, after several studies showing their activity in a spectrum of solid tumors including melanoma.…”
Section: Cdkn2a and Cdk4: A Clinical Perspectivementioning
confidence: 66%
“…The current trial raises a further important issue surrounding cancer drugs that can, by virtue of inhibiting multiple kinases, target the cardiovascular system (e.g., VEGFR or vasculardisrupting agents). In these instances, it could be hypothesized that cells of the vasculature are likely to be exposed to the drug earlier than cells of tumors and possibly at a higher concentration, resulting in cardiovascular adverse events being limiting; for example, the multikinase inhibitor, ilorasertib, targeted the VEGFR and Aurora kinase families resulting in the VEGR-related adverse events being limiting (42). In the case of AT13148, it is difficult to know if the cardiovascular side effects occurred at lower concentrations required for AKT inhibition because the drug inhibits ROCK more potently or because cells in the vascular system are likely to be exposed to such drugs earlier, and to a possibly higher concentration, than cancer cells in the tumor.…”
Section: Discussionmentioning
confidence: 99%